PENINGKATAN NILAI JUAL PRODUK HASIL UMKM MELALUI PELATIHAN PEMBUATAN PERMEN DAN MINUMAN DARI SARI ASAM JAWA - Rani Puspa; Angrian Permana; Iqballulloh Iqballulloh; Suhery Suhery; Khaerul Umam; Intan Rahmania (Yayasan Education and Social Center, 2022)
The implementation of community service activities is an obligation that should be carried out by lecturers and students. This service was carried out in Sindang Mandi Village, Anyar District. The purpose of this service is to improve the skills and welfare of the people by making innovative products from Small and Medium Enterprise. With the innovation of these products, it is hoped that they will be able to provide a better selling value, so that it can increase the profits for business actor. So far, tamarind products are sold only in the form of raw materials, so innovation is needed to make it more developed. Making tamarind candy and tamarind juice drinks, does not require a large additional production cost, but creativity is needed to make tamarind more valuable. The training on making sweets and drinks from tamarind is expected to hone the skills of business actors to be more creative. This training will increase their income. when the training takes place, they will be given methods of packaging and labeling products to make them cleaner and more attractive. In addition, sweets and tamarind drinks are expected to be able to expand market segmentation so that they can be used as favorite products for all people. Through community service activities, in addition, to challenge the lecturers and students to be more creative and innovative, it will also improve the quality and sustainability of the products produced in the future